Experimental research of wall pressure distribution and effect of micro jet at Mach 1.5 - Azami, Muhammad Hanafi; Faheem, Mohammed; Aabid, Abdul; Mokashi, Imran; Khan, Sher Afghan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In this paper, a study on the effect of the control on the wall pressure as well as the quality of the flow when tiny jets were employed. The small jet aimed to regulate the base pressure at the base region of the suddenly expanded duct and wall pressure distribution is carried out experimentally. The convergent-divergent (CD) nozzle with a suddenly expanded duct was designed to observe the wall pressure distribution with and without control using small jets. In order to obtain the results with the effect of controlled four tiny jets of 1 mm diameter located at a ninety-degree interval along a pitch circle diameter (PCD) of 1.3 times the CD nozzle exit diameter in the base, region was employed as active controls. The Mach numbers of the rapidly expanded are 1.5. The jets were expanded quickly into an axis-symmetry duct with an area ratio of 4.84. The length-to-diameter (L/D) ratio of the rapid expansion duct was diverse from 10 to 1. There is no adverse effect due to the presence of the tiny jets on the flow field as well as the quality of the flow in the duct.